2019
DOI: 10.1177/2280800019826517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strontium doping on the biocompatibility of calcium phosphate-coated titanium substrates

Abstract: Background: Titanium biomedical devices coated with strontium-doped calcium phosphate ceramics can support desirable bone regeneration through anabolic and anti-catabolic effects of strontium and the compositions close to that of natural mineral tissue. Methods: Strontium was doped into the calcium phosphate coating using the cyclic pre-calcification method on the anodized titanium plate. The effects of the different concentration of strontium in treatment solution and cycle numbers of the pre-calcification tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
1
11
0
4
Order By: Relevance
“…With regard to biocompatibility, the cell proliferation results showed excellent cell growth capability on Sr-CaP-p. It is worth noting that the enhancement of cell proliferation in the CaP-p group is not significant, which is consistent with some reports (Klymov et al, 2016;Nguyen et al, 2019). Confocal microscopy images showed that cells in the CaP-p group spread well with clear microfilaments while cells in the Sr-CaP-p group had a spindleshaped cell morphology with actively-dividing cells.…”
Section: Discussionsupporting
confidence: 89%
“…With regard to biocompatibility, the cell proliferation results showed excellent cell growth capability on Sr-CaP-p. It is worth noting that the enhancement of cell proliferation in the CaP-p group is not significant, which is consistent with some reports (Klymov et al, 2016;Nguyen et al, 2019). Confocal microscopy images showed that cells in the CaP-p group spread well with clear microfilaments while cells in the Sr-CaP-p group had a spindleshaped cell morphology with actively-dividing cells.…”
Section: Discussionsupporting
confidence: 89%
“…Surface modification is the most effective way to improve biological properties of titanium implants and many inorganic elements are successfully incorporated into titanium coatings ( 4,6,9 ; 11,16 ). Within the elements, Sr exhibits excellent osteogenic potential 4,6,9,14‐16 and Ag shows strong antibacterial capability 3,4,6 . Both elements are successfully incorporated into titanium coatings either singly 9,14‐16 or in combination, 4 but in duplex techniques, which weakens the comprehensive biological properties of coatings and is not convenient for coating preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Within the elements, Sr exhibits excellent osteogenic potential 4,6,9,14‐16 and Ag shows strong antibacterial capability 3,4,6 . Both elements are successfully incorporated into titanium coatings either singly 9,14‐16 or in combination, 4 but in duplex techniques, which weakens the comprehensive biological properties of coatings and is not convenient for coating preparation. Furthermore, short‐term osteogenic and antibacterial capability of these coatings are well documented, 3,6,14,15 but their long‐term effects remain less explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soaking is a low-temperature method that is applicable to substrates of any shape while allowing for the formation of bands with growth factors, antibiotics, etc. [ 8 ].…”
Section: Introductionmentioning
confidence: 99%